Single-stage standard percutaneous nephrolithotomy for a large 8 cm renal calculus - Pawar, Rakesh; Ajmera, Rohit; Yadav, Rohit (Indian Journal of Case Reports, 2025)
Percutaneous nephrolithotomy (PCNL) is a technique used to remove certain stones in the kidney or upper ureter (the tube that drains urine from the kidney to the bladder) that are too large for other forms of stone treatment, such as shock wave lithotripsy or ureteroscopy. Here, we present a case of an extra-large kidney stone (8 cm×6.5 cm) in a 30-year-old male patient, which was removed through a single-puncture PCNL.